Tradition and renovation in Society of Jesus’s education in Spain (Journal of Parents and Teachers, 2016)
In the course 2015-2016, we celebrate golden wedding anniversary of the journal Parents and Teachers which it has been with us in the last 50 years in which the Society of Jesus has been very active in the renovation of the School’s mission, it goes from here my congratulations to all who have made it possible. There are a lot of Jesuits and lays who work together in the Jesuit’s Society, they do it  by his passion for faith and justice, love for the Gospel and education, also it goes through these pages and especially thank all the parents who share with us the same mission: the education of their children.
Keywords: Ignatian pedagogy; Ratio Studiorum; jesuitical education; educational innovation; education.